Morbidity, Physical Disability and Health Security of the Greying Population in India: Distributional Profile and Implications (Indian Journal of Public Health Research & Development, 2020)
Ageing involves multidimensional changes including those in the biological, psychological and socialspheres of a person’s existence. Based on the IHDS 2011-12 the study tries to analyse the morbidity/disability status and the income and expenditure coverage incurred for treatment of the 60 plus folks in thecountry. High Blood Pressure, diabetes and Asthma are the most prevalent morbidity types among the agedpeople and these are suffered through out of the rest of life. The inadequate care and support in the olderage creates stress and makes the infirmity problem more severe. Accessibility and quick improvementin health condition become the major reason for preferring the allopathic treatments. Availing any sort ofpension or health insurance schemes is the possible way that makes the elderly more independent and stable.However the data reveals that the percent of elderly availing these services are slight in number. Financialburden and dependence force them to skip their treatment or to ignore the affliction, this makes their healthcondition more severe and further leads to more illness.
Keywords: Health, Health care, Health Security, Ageing